Immigrant Mothers’ De/Motivational Factors on Early Childhood Education & Care in Southwest, Finland - Hasan, Mohammad (My University, 2023)
This study aims at exploring the de/motivational factors of immigrant mothers on Early Childhood Education and Care in Southwest, Finland. It also focuses on the experiences of mothers who were raised outside of Finland and their children who are currently being raised in Finland, in regards to early childhood education and care (ECEC) in Finland. It also examines the expectations and learning goals that these mothers have for their children in Finnish daycare. Finland is known for being a welcoming country for immigrants, and this study aims to understand how the ECEC system in Finland impacts the lives of immigrant families and their children. The theoretical perspectives used in this study were: social capital by Bourdieu and its application by Coleman. These perspectives helped to explain the social networks of the parents and their norms & values in upbringing their children. This study gathered data from mothers living in the southwest region of Finland through interviews. The sampling process for this study was a combination of purposive sampling, in which specific individuals were selected because they fit certain criteria, and convenient sampling, in which individuals were selected because they were readily available and willing to participate. This study sought to understand the experiences and perspectives of these mothers on ECEC in Finland, as well as their expectations and learning goals for their children in Finnish daycare. Following the interview questions, five major categories, sub-categories were also made during the process. Among five major themes, four of them were related to the mothers’ motivating factors and one of them was related to the mothers’ demotivating factor regarding Finnish daycare. Analysis revealed that cultural norms and values are the most important factor for the mothers to send their children to the daycare. Although some of them are satisfied with the way their children are being brought up in Finland, others are concerned about their own cultural norms & values are being affected by it. Whereas, others are happy to combine both of the ways and trying to find a common ground so that their children get benefitted from both of the societies. Fears and cultural conflicts have been the most common reasons among the mothers which are demotivating them to enroll their children to the Finnish daycares in Southwest, Finland.